Ambulance clinical placements – A pilot study of students' experience - Boyle, Malcolm J (BioMed Central, 2008)
BACKGROUND: Undergraduate paramedic students undertake clinical placements in a variety of locations. These placements are considered an essential element for paramedic pre-employment education. However, anecdotal evidence suggests some students have not had positive experiences on their emergency ambulance placements. The objective of this study was to identify the type of experiences had by students during ambulance clinical placements and to provide feedback to the ambulance services. METHODS: In this pilot study we employed a cross-sectional study methodology, using a convenience sample of undergraduate paramedic students available in semester one of 2007 to ascertain the students' views on their reception by on-road paramedics and their overall experience on emergency ambulance clinical placements. Ethics approval was granted. RESULTS: There were 77 students who participated in the survey, 64% were females, with 92% of students < 25 years of age and 55% < 65 Kg in weight. There was a statistically significant difference in average height between the genders (Male 179 cm vs Female 168 cm, p < 0.001). Clinical instructors were available to 44% of students with 30% of students excluded from patient management. Thirty percent of students felt there was a lot of unproductive down time during the placement. Paramedics remarked to 40% of students that they doubted their ability to perform the physical role of a paramedic, of this group 36% were advised this more than once. CONCLUSION: This study demonstrates that for a small group of students, emergency ambulance clinical placements were not a positive experience clinically or educationally. Some qualified paramedics doubt if a number of female students can perform the physical role of a paramedic.